Systematics of the genus Oecomys (Sigmodontinae: Oryzomyini): molecular phylogenetic, cytogenetic and morphological approaches reveal cryptic species. Issue 1 (18th December 2017) - Suárez-Villota, Elkin Y; Carmignotto, Ana Paula; Brandão, Marcus Vinícius; Percequillo, Alexandre Reis; Silva, Maria José de J
Abstract: Oecomys is a genus of Neotropical arboreal rodents composed of 17 species with diploid number ranging from 2 n = 54 to 86. Despite this high taxonomic and karyotypic diversity, the species-level systematics remains uncertain. We investigated the phylogenetic relationships and species delimitation of Oecomys using multiple approaches based on cytogenetic, molecular (mtDNA and nuDNA sequences) and morphological data sets. Sampling included 73 individuals from 25 localities in Amazonia, Cerrado, Pantanal and the Atlantic Forest, as well as 128 DNA sequences from GenBank. Molecular species boundaries associated with karyotype, morphological characters and geographic distribution led us to recognize 15 distinct lineages in Oecomys . These include five major well-supported clades composed of O. bicolor, O. catherinae, O. cleberi, O. mamorae, O. paricola and O. roberti, which were hypothesized as species complexes with at least eight putative new taxa. Three new karyotypes are also reported for the genus: 2 n = 54 (FN = 54), 2 n = 62 (FN = 62) and 2 n = 70 (FN = 74). Sympatry of up to four species with different diploid numbers recovered in distinct clades illustrates the complex evolutionary history in Oecomys . These data highlight the importance of combining cytogenetic, morphological and geographic information along with molecular coalescent analyses in developing species delimitation scenarios.